Integration of Educational Technology: Enhancing Prose and Poetry Creativity Through Digital Media in Elementary Schools - Shintarahayu, Balqis (CV. Bimbingan Belajar Assyfa, 2025)
Technology integration in the Indonesian Language curriculum in elementary schools is becoming increasingly important in today's digital era. This study examines the use of creative applications and digital platforms to enrich prose and poetry learning for grade 5 students. With a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, we developed a web-based learning media called